# Differentiate the function 2(1+sqrtx)-ln(1+sqrtx)^2

### 1 Answer | Add Yours

Since we recognize composed functions in the given expression, we'll differentiate the expression using the chain rule.

If we have the composed function u(v(x)), then the chain rule is:

[u(v(x))]' = u'(v)*v'(x)

f(x) = 2(1+sqrtx) - ln(1+sqrtx)^2

We'll consider the function ln(1+sqrtx)^2 as a composed function an we'll differentiate it using the chain rule:

[ln(1+sqrtx)^2]' = [1/(1+sqrtx)^2]*[(1+sqrtx)^2]'*(1+sqrtx)'

[ln(1+sqrtx)^2]' = [2(1+sqrtx)/(1+sqrtx)^2]*(1/2sqrtx)

We'll simplify and we'll get:

[ln(1+sqrtx)^2]' = 1/sqrt x*(1+sqrtx)

We'll remove the brackets:

[ln(1+sqrtx)^2]' = 1/(x + sqrt x)

Now, we'll substitute the result in the expression of the derivative of f(x):

f'(x) = [2(1+sqrtx) - ln(1+sqrtx)^2]'

f'(x) = 1/sqrtx - 1/sqrt x*(1+sqrtx)

f'(x) = (1+sqrt x - 1)/sqrt x*(1+sqrtx)

We'll eliminate like terms from numerator:

f'(x) = (1+sqrt x - 1)/sqrt x*(1+sqrtx)

f'(x) = sqrt x/sqrt x*(1+sqrtx)

We'll simplify and we'll get:

**f'(x) = 1/(1+sqrtx)**